(untitled) - Belloni, Mario (Upper Saddle River, N.J., 2006)
PhysletA (R) Quantum Physics contains a collection of over 200 ready-to-run interactive exercises. These "media-focused" critical thinking and problem-solving exercises are based on carefully designed computer simulations generated in awardwinning Java applets. PhysletA (R) Quantum Physics is based on current educational, experimental, and theoretical research, and gives students an interactive visual representation of the often difficult-to-visualize physical phenomena in quantum physics.
Keywords: Quantum theory,Quantum theory; Problems, exercises, etc.,Computer-assisted instruction,Textbooks